Keluarga Sakinah dalam Tradisi Mamacah pada Rokat Pandhabah Manten - Rahmawati, Yeni Tri Nur; Hamdanah, Hamdanah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study investigates the Mamaca tradition, a prominent oral literary heritage of the Madurese and Pandalungan communities in East Java, characterized by the melodic chanting of ancient didactic texts. The research aims to analyze the socio-ideological role of Mamaca in instilling moral and ethical values, such as filial piety and respect for educators. Employing semiotic and ethnolinguistic approaches, the study explores the structural and symbolic meanings embedded in various genres, including epics and hagiographies of the prophets. Despite its significance as a vehicle for philosophical and religious transmission, the tradition faces potential extinction due to the proliferation of modern entertainment and a critical lack of regeneration among the youth. The findings highlight current revitalization efforts by customary institutions, academics, and the government to reintegrate Mamaca into formal education, specifically within local language curricula, to preserve regional etiquette (tata krama). The study concludes that the integration of Mamaca’s aesthetic and ethical values into the educational sphere is a vital strategy for cultural sustainability. This approach ensures that local wisdom remains a relevant foundation for character building amidst the shifting sociocultural landscape of contemporary Indonesia.